Scanography: photographic art between the realms of sight and touch - Jane Vuorinen (Journal of Aesthetics & Culture)
Scanographs are photographs made using a scanner, and they have become increasingly present in contemporary photographic art in the expanded field. In this article, I examine the artistic processes of three artists working with scanners and analyze their works through their relationships with the senses of sight and touch. These works open up spaces for a haptic gaze, where the tactile qualities of the working processes of the artists are mediated through the images. I use theoretical sources centering on sight and touch, presence and absence, analogue and digital to suggest ways of considering these qualities not as opposing characteristics but rather as simultaneous polarities.